The Application of Total Quality Management in Higher Education Institutions - Al-Sharif, Abdul Qader bin Issa (Arab Journal for Sciences and Research Publishing, 2015)
The aim of this study is to present the main concepts of management in institutions of higher education, and its orientation towards the implementation of total quality management in order to improve the quality of higher education services.In the light of this communication, particular attempt to analyze the levels of satisfaction with the various agencies that make up the labor market in Algeria to the different services (output) presented by the Algerian university.
Keywords: quality; total quality management; higher education in Algeria; labor market institutions; higher education outcomes